2020
DOI: 10.21203/rs.3.rs-86723/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteriophage cocktail supplementation improves growth performance, gut microbiome and production traits in broiler chickens

Abstract: Background: Effective antibiotic alternatives are the urgent need of poultry industry to control disease outbreaks. Phage therapy mainly utilizes lytic phages to kill their respective bacterial hosts and can be attractive solution to combating the emergence of antibiotic resistance in livestock. Methods: Five hundred and four one-day--old broilers (Ross 308) were allotted into 1 of 4 treatment groups according to a completely randomized design. Dietary treatments consisted of CON (basal diet), PC (CON + 0.025%… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Regarding spleen weight ratio, the benefit of treating The Efficiency of Bacteriophages Against Salmonella Typhimurium Infection in Native Noi Broilers chicken with phages was not demonstrated compared to those from Kim et al (2013), whose results showed a drop in spleen weight relative to body weight, indicating that phage inclusion was better. The current outputs are consistent with the findings of Upadhaya et al (2021), who discovered that the relative weight of the gizzard increased more substantially in the positive control group than the control and phage groups, which could be explained by an increase in feed intake in the positive control group. On the other hand, supplementation with anti-S. Enteritidis bacteriophage did not affect the relative weight of organs after 35 days (Kim et al, 2013).…”
Section: Carcass Characteristics and Internal Organs Of Noi Chickenssupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding spleen weight ratio, the benefit of treating The Efficiency of Bacteriophages Against Salmonella Typhimurium Infection in Native Noi Broilers chicken with phages was not demonstrated compared to those from Kim et al (2013), whose results showed a drop in spleen weight relative to body weight, indicating that phage inclusion was better. The current outputs are consistent with the findings of Upadhaya et al (2021), who discovered that the relative weight of the gizzard increased more substantially in the positive control group than the control and phage groups, which could be explained by an increase in feed intake in the positive control group. On the other hand, supplementation with anti-S. Enteritidis bacteriophage did not affect the relative weight of organs after 35 days (Kim et al, 2013).…”
Section: Carcass Characteristics and Internal Organs Of Noi Chickenssupporting
confidence: 91%
“…For example, in experiments using diets containing phages against S. Gallinarum, S. Typhimurium, and S. Enteritidis, where broiler chickens were raised under normal physiological conditions (without bacterial challenge), improvements in body weight and FCR were observed (Lim et al, 2010;Kim et al, 2014;Wójcik et al, 2020). This is due to the fact that the bacteriophage inhibits the growth of bacteria in the broilers' gastrointestinal tract (Lim et al, 2010), and the increase in body weight may be related to an increase in feed intake (Upadhaya et al, 2021). However, not all cases of phage therapy or phage supplementation in diets resulted in enhanced broiler production traits.…”
Section: Effects Of Bacteriophage Treatments On Production Performanc...mentioning
confidence: 99%
See 1 more Smart Citation
“…can quickly create a complex bacterial community and protect the host from harmful bacteria infections. In addition, the intestinal microbiota affects the physiological development, health, and productivity, leading to the hypothesis that the use of feed additives such as organic acids can be useful to control microbial community (Upadhaya et al, 2021). Previously, Kim et al (2014) reported that Prevotella and Arcobacter are important acetate-producing bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al reported the administration of a phage cocktail to four patients in a COVID-19 intensive care unit in China was able to treat carbapenem-resistant A. baumannii infection, otherwise showing the insurgence of phage-resistant A. baumannii strains when only one phage was administered [62]. The application of a cocktail of bacteriophages has also been demonstrated to be an effective substitute to antibiotic growth promoter replacement in broiler diets [63], which would further assist to reduce development of anti-microbial resistance arising from poultry production. The combination of phages (φkm18p, φTZ1 and φ314) as a cocktail was able to decrease the concentration of A baumannii in another study in contrast to single-phage administration, otherwise correlated to recidivist bacterial growth [64].…”
Section: Cocktail Therapymentioning
confidence: 99%